Extremal ω-plurisubharmonic functions as envelopes of disc functionals: generalization and applications to the local theory - Magnússon, Benedikt Steinar (MATHEMATICA SCANDINAVICA, 2012)
We generalize the Poletsky disc envelope formula for the function {uPSH(X,ω); u≤ φ} on any complex manifold X to the case where the real (1,1)-current ω=ω_1-ω_2 is the difference of two positive closed (1,1)-currents and φ is the difference of an ω_1-upper semicontinuous function and a plurisubharmonic function.